Technology Acceptance Model Approach, Subjective Norm Towards Behavior Intention Is Mediated By Attitude And Moderated By Religiosity - Rahmanda, Ghina; Abdurrahman, Abdurrahman (Jurnal Ekonomi, 2024)
This study aims to examine the factors that encourage individuals to donate using the Kitabisa.com platform. This study was made to explore the influence of perceived usefulness, perceived ease of use, subjective norms, behavior, intention to use, moderated by religiosity and mediated by attitude. Data were collected through a survey using a questionnaire distributed online to millennial groups who use the platform. Data were analyzed using the Structural Equation Model (SEM). The findings in this study are that perceived usefulness and Perceived ease of use have a positive effect on attitude. Subjective norms have a positive effect on attitude. Attitude has a positive effect on behavioral intention to use. Perceived usefulness does not affect behavioral intention to use. Perceived ease of use does not affect behavioral intention to use. Religiosity is unable to moderate the relationship between perceived usefulness, perceived ease of use and subjective norms on attitude.